Effectiveness of Proactive Medical-Psychological Support in Patients with Psychosomatic Comorbidity - Savchenko, Veronika (Psychosomatic Medicine and General Practice, 2026)
Relevance. In the modern world, there is a growing trend toward increased psycho-emotional load, which significantly raises the risk of developing somatic diseases and complicates their course. Despite a large body of research in the field of psychosomatics, questions remain regarding the effectiveness of short-term комплекс interventions aimed at integrating medical and psychological approaches. Particular attention should be paid to evaluating proactive support models that can ensure not only symptom reduction but also sustainable changes in patients’ psycho-emotional state. Objective. To assess the effectiveness of proactive medical-psychological support in patients with psychosomatic comorbidity by analyzing the dynamics of psycho-emotional indicators before and after a 6–8-week psychological intervention. Materials and Methods. The study involved 32 respondents with signs of psychosomatic comorbidity, the sample was divided into two cohorts: somatically oriented and psychologically oriented. The psycho-emotional state was assessed using standardized psychodiagnostic instruments: 4DSQ questionnaire (somatization, distress, anxiety, depression); SCL-90-R questionnaire (somatoform disorders, anxiety, depression); Perceived Stress Scale (PSS-10); Quality of Life Scale (CQLS). Results. Initial psychodiagnostic assessment showed that the sample was characterized by elevated levels of distress, somatization, and perceived stress, as well as moderate levels of anxiety and depression, while quality of life indicators were significantly reduced. Correlation analysis revealed statistically significant relationships between psycho-emotional and somatic indicators. The strongest positive correlation was found between depression scores across different questionnaires (ρ = 0.827; p < .001). Significant associations were also identified between distress, somatization, and depression, while quality of life indicators showed negative correlations with levels of depression, distress, and somatization (p < .05–.001). After the implementation of the 6–8-week proactive medical-psychological support, a statistically significant reduction in somatization, distress, anxiety, depression, and perceived stress was observed (p < .001), along with an improvement in patients’ quality of life. The results of the paired Student’s t-test confirmed the reliability of these changes, while effect sizes (Cohen’s d > 0.8) indicated high practical significance. Cluster analysis demonstrated a positive restructuring of psycho-emotional profiles following the intervention, with an increase in adaptive states and a decrease in distress-depressive states. The results of one-way ANOVA confirmed statistically significant differences between clusters, indicating a heterogeneous effect of the intervention. Discussion. The obtained results indicate a close relationship between psychological and somatic manifestations in patients with psychosomatic comorbidity. The identified correlations are consistent with contemporary views on the significant role of emotional tension, distress, depression, and anxiety in the development of somatic symptoms. The positive dynamics observed after the implementation of proactive medical-psychological support indicate the effectiveness of a comprehensive approach that considers not only the somatic nature of the disease but also its psychological components. The significant reduction in perceived stress, anxiety, somatization, and depression may be associated with increased patient awareness of their condition and the development of more adaptive coping strategies. Particularly important is the improvement in quality of life, which reflects not only a reduction in symptoms but also an overall enhancement of subjective well-being. This underscores the relevance of using a proactive approach in working with patients with psychosomatic disorders. At the same time, the presence of clusters with less pronounced positive dynamics indicates the need for personalized interventions and consideration of individual psycho-emotional profiles, opening prospects for further research in individualized proactive medical-psychological support. Conclusion. It has been established that psycho-emotional factors play a significant role in the development and maintenance of somatic symptoms, and their increase is associated with a decrease in patients’ subjective well-being. The implementation of proactive medical-psychological support demonstrated a pronounced positive dynamic in the psychological state of respondents, reflected in reduced symptom severity and improved quality of life. These changes are not only statistically significant but also practically meaningful, confirming the effectiveness of the applied approach. At the same time, the results indicate heterogeneity in psycho-emotional profiles and varying sensitivity to psychological intervention, highlighting the importance of personalization in proactive medical-psychological support. Overall, the study confirms the feasibility of using a proactive approach as an effective tool for optimizing psychological well-being and improving quality of life in patients with psychosomatic comorbidity. Keywords: psychosomatic comorbidity, psycho-emotional disorders, psychosomatics, proactive approach, proactive medical-psychological support, somatization, distress, psychological intervention.